Can post‐treatment free PSA ratio be used to predict adverse outcomes in recurrent prostate cancer?. (26th September 2020) - Goldberg, Hanan; Glicksman, Rachel; Woon, Dixon; Hoffman, Ally; Shaikh, Hina; Chandrasekar, Thenappan; Klaassen, Zachary; Wallis, Christopher J.D.; Ahmad, Ardalan E.; Sanmamed‐Salgado, Noelia; Qu, Xuanlu; Moraes, Fabio Y.; et al.
Abstract : Objectives: To assess whether free PSA ratio (FPSAR) at biochemical recurrence (BCR) can predict metastasis, castrate‐resistant prostate cancer (CRPC), and cancer‐specific survival (CSS), following therapy for localised disease. Patients and Methods: A single‐centre retrospective cohort study (NCT03927287) including a discovery cohort composed of patients with an FPSAR after radical prostatectomy (RP) or radiotherapy (RT) between 2000 and 2017. For validation, an independent Biobank cohort of patients with BCR after RP was tested. Using a defined FPSAR cut‐off, the metastasis‐free‐survival (MFS), CRPC‐free survival, and CSS were compared. Multivariable Cox models determined the association between post‐treatment FPSAR, metastases, and CRPC. Results: Overall, 822 patients (305 RP‐ and 363 RT‐treated patients and 154 Biobank patients) were analysed. In the RP cohort, a total of 272/305 (89.1%) and 33/305 (10.9%) had a FPSAR test incidentally and reflexively, respectively. In the RT cohort, 155/363 (42.7%) and 208/263 (57.3%) had a FPSAR test incidentally and reflexively, respectively. However, in the prospective Biobank RP cohort, FPSAR testing was done on all samples of patients diagnosed with BCR. A FPSAR cut‐off of 0.10 was determined using receiver operating characteristic analyses in both the RP and RT cohorts. A FPSAR of <0.10 resulted in longer median MFS (14.8 vs 9.3 years and 14.8 vs 13 years, respectively), and longer median CRPC‐free survival (median not reached vs 9.9 years and 20.7 vs 13.8 years, respectively). Multivariable analyses showed that a FPSAR of ≥0.10 was associated with increased metastasis in the RP cohort (hazard ratio [HR] 1.915, 95% confidence interval [CI] 1.241–2.955) and RT cohort (HR 1.754, 95% CI 1.112–2.769), and increased CRPC in the RP cohort (HR 2.470, 95% CI 1.493–4.088). Findings were validated in the Biobank cohort. Conclusions: A post‐treatment FPSAR of ≥0.10 is associated with more aggressive disease, suggesting a potentially novel role for this biomarker.